Adaptation of the Learned Helplessness Scale in Brazil - Couto, Cleno (2023)
The present study aimed to adapt the Learned Helplessness Scale (LHS) to Brazilian Portuguese and assess its psychometric properties and nomological network in a Brazilian sample. Participants completed an online survey that consisted of the LHS, Rosenberg’s Self-Esteem Scale, and the Perceived Stress Scale. 429 people participated, aged 18-79, mostly women, from multiple regions of Brazil and socioeconomic status. Exploratory and Confirmatory Factor Analysis suggested a unidimensional solution with 18 items as appropriate. Correlations between the LHS and the other instruments also provided evidence of the expected nomological relationships. And we assessed the differences in LHS scores by sociodemographic data. These findings are favorable to the use of this instrument in Brazilian samples.